Association between healthy eating index-2015 scores and metabolic syndrome among Iranian women: a cross-sectional study - Mohammad-Reza Jowshan; Maryam Rafraf; Amir-Hossein Hashemi; Samaneh Hajjarzadeh; Mohammad Asghari-Jafarabadi; Somayyeh Asghari (BMC, 2024)
Abstract Background Metabolic syndrome (MetS) is one of the leading public health issues in the world with a reported prevalence of nearly 25% in the past decades in Iran. The present research aimed to identify the association between the Healthy Eating Index (HEI) and MetS components among female teachers. Methods In this cross-sectional study, 97 female teachers aged 31-57 years were enrolled from 2018 to 2019 in Qom, Iran. Usual dietary intakes were assessed using a validated 168-item Food Frequency Questionnaire (FFQ). HEI-2015 was calculated according to the consumption of whole fruits, vegetables, protein foods, beans, seafood, plant proteins, total and refined grain, dairy, fatty acid ratio, saturated fats, added sugars, and sodium. We also measured anthropometric and biochemical parameters. To evaluate the association between HEI-2015 and MetS, multivariate logistic regression was performed. Results MetS was found in 59.8% of participants. Total HEI-2015 scores were significantly lower in participants with MetS compared to those without MetS (59.69 ± 8.98 vs. 64.21 ± 8.71, respectively; p = 0.02). Daily energy intake, weight, body mass index, waist circumference, systolic and diastolic blood pressure, serum triglyceride, and fasting blood sugar levels were higher in women with MetS (all p < 0.05). Higher HEI-2015 total scores (OR: 0.94; 95% CI: 0.89-0.99; p = 0.02) and scores of total vegetables (OR: 0.62; 95% CI: 0.42-0.91; p = 0.02), dark green vegetables and beans (OR: 0.62; 95% CI: 0.39-0.98; p = 0.04), fatty acid ratio (OR: 0.83; 95% CI: 0.68-0.99; p = 0.04), refined grain (OR: 0.86; 95% CI: 0.75-0.99; p = 0.04), and added sugars (OR: 0.44; 95% CI: 0.26-0.75; p = 0.002) were all associated with lower odds of having MetS. Conclusions Higher HEI-2015 scores, particularly in total vegetables, dark green vegetables, beans, and fatty acid ratio, as well as refined grain and added sugars were found to be associated with reduced odds of having MetS among Iranian female teachers. However, further prospective studies are required to confirm this finding.